A100 THE ROLE OF EPS8 IN THE PATHOGENESIS OF PEDIATRIC INFLAMMATORY BOWEL DISEASE. (15th March 2019) - Long, K; Li, Q; Guo, C; Warner, N; Zhang, S; Pan, J; Leung, G; Batura, V; Muise, A
Abstract: Background: The rate of onset for inflammatory bowel disease (IBD) is rising worldwide—most significantly in the pediatric population. The pathogenesis of the disease involves a complicated interaction between the environment and genetics. Recent findings suggest that there is a broad range of rare, single-gene mutations that correlated with the IBD phenotype in children. Some of these single-gene defects can disrupt the epithelial barrier, which alters intestinal immunity. Rare mutations in the Epidermal Growth Factor Receptor Substrate 8 ( EPS8 ) gene has been reported in pediatric patients who presented with pancolitis, colonic strictures and other IBD-like symptoms. EPS8 has been shown to be involved in regulating actin polymerization; previously literature suggests that loss of EPS8 results in disruption of intestinal microvilli in C. Elegans and mice. The functional role of EPS8 in the pathogenesis of very early onset IBD remains elusive. Aims: We want to elucidate how a mutation in the EPS8 gene (I700T) affects the structure of a patient's epithelial barrier. Ultimately, we want to clarify how the EPS8 variant contributes to the onset of pediatric IBD. We hypothesize that the EPS8 mutation will cause abberations in the actin structure of the patient's intestinal epithelia. Methods: A pediatric patient with IBD was screened using whole exome sequencing (WES). Colon samples from the patient were collected and localization of EPS8 was visualized using immunofluorescence microscopy. Morphology of the intestinal microvilli will be assessed using transmission electron microscopy. Co-immunoprecipitation and immunoblot will be performed to evaluate the interaction of EPS8 signalling complex, which is involved in actin dynamics. Results: WES data identified a patient with a homozygous recessive missense mutation in EPS8 (I700T), which was confirmed by Sanger sequencing. Immunofluorescence staining of the colonic sections revealed lower co-localization of EPS8 and beta-actin on the apical surfaces of epithelial cells, compared to IBD and normal controls. We predict that closer examination of the cell structure using electron microscopy will show disruption of the microvilli in the EPS8 mutant. Conclusions: Current findings suggest that the EPS8 mutant may disrupt microvilli actin organization in intestinal epithelial cells, which could contribute to the pathophysiology of pediatric IBD. Future experiments, such as intestinal organoid models, are necessary to confirm these results. Funding Agencies: CIHR